Metal on metal total hip arthroplasty and a large groin mass: Not always adverse reaction to metallic debris - Krishnan, Harry (Int J Surg Case Rep, 2014)
Due to their improved wear rates, Metal-on-metal bearings have been increasingly used in the past decade by orthopaedic surgeons carrying out total hip arthroplasty. However there is increasing evidence that there are significant complications associated with such implants. One well documented complication is that of metallic debris leading to pseudotumour formation, however there is less known about associations with other tumours within the pelvis. We present two cases where an intra-pelvic mass in patients with metal-on-metal implants were diagnosed as being of a different aetiology. This highlights the need for careful assessment of such patients in order to guide appropriate management.